Efeitos tardios dos praguicidas organoclorados no homem - Nunes, Mônica Vannucci; Tajara, Eloiza Helena [UNESP] (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 1998)
Procurou-se relacionar as informações disponíveis sobre os organoclorados e os efeitos crônicos provocados pela exposição. Os compostos organoclorados são os praguicidas mais persistentes já fabricados. Embora sejam geralmente eficientes no controle das pragas, são importantes poluentes ambientais e potenciais causas de problemas de saúde para o homem, tendo sido proibidos ou controlados na maioria dos países. Com poucas exceções, os efeitos tardios desses compostos sobre a saúde humana são difíceis de detectar, em função de dificuldades metodológicas e da extrapolação dos resultados. A genotoxicidade está entre os mais sérios dos possíveis danos causados por esses compostos e merece atenção especial, devido à natureza irreversível do processo. Outro ponto a ser considerado é o aumento na incidência de alterações no desenvolvimento do trato reprodutivo e na fertilidade masculina observada nas últimas décadas provavelmente decorrente do aumento da exposição intra-uterina a compostos estrogênicos e anti-androgênicos, como os organoclorados.

Available information on organochlorines and the chronic effects of exposure to them are set out. Organochlorinated compounds are the most persistent pesticides and can be found in all ecosystems. Although they are generally efficient in pest control, they are also a potent environment pollutant and can provoke health problems in man. The evidences of the carcinogenic potential of organochlorines are controversial and insufficient, but they have been related to an increase in the incidence of some kinds of tumors, such as leukemia and solid tumors. Reproductive effects, due to anti-androgenic and estrogenic action, on embryonic virilization, the incidence of abortion and the frequency of prematurity, have also been observed. The accumulation of the organochlorines in the adipous tissue is positively correlated to the increase in aging and could be implicated in the development of aging diseases, such as Parkinson's disease. The effects of pesticides on human health have not yet been completely elucidated. Genotoxicity is one of the most serious of the possible harmful effects caused by these compounds and calls for special attention in view of the irreversible nature of the process and to the long latency associated with its manifestation.
Delayed effects of organochlorine pesticides in man
Keywords: Praguicidas; Leucemia; Exposição a praguicidas; Pesticides; Leukemia; Pesticide exposure